Ingrained: An Automated Framework for Fusing Atomic‐Scale Image Simulations into Experiments. Issue 19 (5th April 2022) - Schwenker, Eric; Kolluru, Venkata Surya Chaitanya; Guo, Jinglong; Zhang, Rui; Hu, Xiaobing; Li, Qiucheng; Paul, Joshua T.; Hersam, Mark C.; Dravid, Vinayak P.; Klie, Robert; Guest, Jeffrey R.; Chan, Maria K. Y.
Abstract: To fully leverage the power of image simulation to corroborate and explain patterns and structures in atomic resolution microscopy, an initial correspondence between the simulation and experimental image must be established at the outset of further high accuracy simulations or calculations. Furthermore, if simulation is to be used in context of highly automated processes or high‐throughput optimization, the process of finding this correspondence itself must be automated. In this work, "ingrained, " an open‐source automation framework which solves for this correspondence and fuses atomic resolution image simulations into the experimental images to which they correspond, is introduced. Herein, the overall "ingrained" workflow, focusing on its application to interface structure approximations, and the development of an experimentally rationalized forward model for scanning tunneling microscopy simulation are described. Abstract : The "ingrained" framework is a tool for finding useful approximations of atomistic structures observed in scanning tunneling microscopy/scanning transmission electron microscopy imaging. The framework establishes this "simulated fit‐to‐experiment" in an automated and robust way, coupling programmatic structure initialization and forward modeling with image registration.